A Study of Sunaryo’s Wot Batu through Art Criticism - Khairunnisa Liummah (Journal of Visual Art and Design, 2022)
The Indonesian modern art scene in the 1940s, which related to many ideologies, also influenced the art of Indonesian artist Sunaryo (1943). One of his recent works, Wot Batu, is a work of land art consisting of sequential installations made with stones lying in a landscape in Bandung. Wot Batu means ‘stone bridge’ in old Javanese. This study aimed to discover Sunaryo’s artistic qualities in Wot Batu in order to trace Sunaryo’s perspective of spirituality and his background as a modern Indonesian artist. This research used Feldmann’s art criticism approach. The interpretation and judgment process in this work was obtained by connecting a formal analysis of the artwork to Sunaryo’s background as an artist. The research findings confirm that Sunaryo presents his own perspective on spirituality in this work through the use of stones as the main material and other natural elements. He made use of various aspects, such as combining and assembling stones, multisensory stimulation of the visitor, the site and the movement of the visitor inside it, support his concept. This study revealed that Sunaryo’s perspective on spirituality not merely concerns the relationship between humans and a greater power, but also humans as a part of nature, balance, the perpetuity of the universe, and the experience of nothingness and serenity.